Methodological implications of assumptions in science - Boczar, Janusz (Folia Philosophica, 2000)
The author of the present article draws the reader’s attention to the fact that all theories and research methods have their place on the list of assumptions known as axioms, theses, or simply assumptions. In this way the area of science is invaded by conventionalism, scientific relativism, that is by the so called background. These are the weakest points of every science.